HCN/HNC chemistry in shocks: a study of L1157-B1 with ASAI. Issue 1 (24th July 2021) - Lefloch, B; Busquet, G; Viti, S; Vastel, C; Mendoza, E; Benedettini, M; Codella, C; Podio, L; Schutzer, A; Rivera-Ortiz, P R; Lépine, J R D; Bachiller, R
ABSTRACT: Hydrogen cyanide (HCN) and its isomer hydrogen isocyanide (HNC) play an important role in molecular cloud chemistry and the formation of more complex molecules. We investigate here the impact of protostellar shocks on the HCN and HNC abundances from high-sensitivity IRAM 30 m observations of the prototypical shock region L1157-B1 and the envelope of the associated Class 0 protostar, as a proxy for the pre-shock gas. The isotopologues H 12 CN, HN 12 C, H 13 CN, HN 13 C, HC 15 N, H 15 NC, DCN, and DNC were all detected towards both regions. Abundances and excitation conditions were obtained from radiative transfer analysis of molecular line emission under the assumption of local thermodynamical equilibrium. In the pre-shock gas, the abundances of the HCN and HNC isotopologues are similar to those encountered in dark clouds, with an HCN/HNC abundance ratio ≈1 for all isotopologues. A strong D-enrichment (D/H ≈ 0.06) is measured in the pre-shock gas. There is no evidence of 15 N fractionation neither in the quiescent nor in the shocked gas. At the passage of the shock, the HCN and HNC abundances increase in the gas phase in different manners so that the HCN/HNC relative abundance ratio increases by a factor 20. The gas-grain chemical and shock model uclchem allows us to reproduce the observed trends for a C-type shock with pre-shock density n (H) = 10^5cm^-3 and shock velocity V_ s= 40kms^-1 . We conclude that the HCN/HNC variations across the shock are mainly caused by the sputtering of the grain mantle material in relation with the history of the grain ices.